Business strategies and local effects: the integration of small farmers into the pulp and paper industry - de Aquino, Silvia Lima (Universidade Federal Rural do Rio de Janeiro, 2015)
Fibria Celulose S/A (a multinational corporation resulting from the junction between Aracruz Celulose S/A and Votorantim CP), has been integrating small farmers to its industry through a program now known as "Produtor Florestal". After signing a contract with the company, these farmers cultivate eucalyptus that will be used in the production of cellulose. The purpose of this communication is to address a reflection on the changes caused by the spread of eucalyptus and the conflicts arouse since than in the life, work and ownership organization of small farmers from a large food producer region in southwest highlands of Espírito Santo state. Therefore, we propose a discussion based on the analysis of ethnographic information, which allow us to access the impressions of small farmers about these issues. The information was seized through fieldwork - such as participant observation and interviews - with small farmers from this region who integrated this industry and also those who resisted it. The fieldwork took place by the months of August to October 2011 in the town Domingos Martins - ES.